Effectiveness of carbon dioxide cryotherapy for the treatment of cutaneous leishmaniasis: Systematic review and meta-analysis. - Feleke Tilahun Zewdu; Bisrat Misganaw Geremew; Endalamaw Gadisa Belachew; Kassahun Alemu Gelay (PLoS Neglected Tropical Diseases)
Background Cutaneous leishmaniasis is one of the neglected tropical diseases which is hard to treat. Carbon dioxide-based cryotherapy is a novel therapeutic option for cutaneous leishmaniasis in both developed and developing nations. This study aims to summarize the pooled evidence on the effectiveness of carbon dioxide-based cryotherapy for the treatment of cutaneous leishmaniasis. Methods Searches of grey literature using Google Scholar and databases including PubMed, Scopus, EMBASE, Web of Science, and Google Scholar were conducted to find studies that reported the cure rate of cryotherapy. The search, screening, data extraction, and critical evaluation were carried out by two authors, with a third acting as a tiebreaker. To locate papers, we used Medical Subject Headings (MeSH) phrases and keywords. Between May 10 and May 13, 2023, the review protocol was developed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 checklist. For the meta-analysis, STATA 17 was the statistical software used. The random effects model was employed to compile the effect estimates. Lastly, we used the funnel plot and Egger's test to evaluate publication bias, heterogeneity, sensitivity, and subgroup analyses. Result Out of the 16 researches included in the review, seven papers with a total of 1,357 cases were chosen for the meta-analysis. For the treatment of cutaneous leishmaniasis, the pooled cure rate with carbon dioxide-based cryotherapy was 87.84% (95% CI: 65.92-109.77). Randomized controlled trials made up the majority of the studies that were used. The highest cure rate was seen when there were two lesions, 94.34% (95% CI:68.21-119.48), and when the size of the lesion was less than or equal to 4, 93.83% (95% CI:68.92-118.75). There was no indication of a significant publishing bias. Conclusion Carbon dioxide-based cryotherapy revealed a high pooled efficacy. The efficacy of the CL instances was mostly dependent on the extent of the lesion and the frequency of therapy administration. To determine if this therapy is beneficial in a routine care context, a large-scale study with a sound design is necessary.